"Uma cidade condenada aos sofrimentos": os mecanismos legais urbanísticos no processo de regulação e controle sanitário em Juiz de Fora/MG (1887-1942) - Moratori, Daniel de Almeida (2024)
The intensification of health and environmental problems in Juiz de Fora/MG, at the end of the century. XIX and in the first decades of the century. XX, came mainly from its accelerated physical demographic expansion, heavy rainfall and floods, which encouraged pertinent debates and mitigating actions regarding it. As the main economic center in the southeast of Minas Gerais (Zona da Mata), a confluence of factors led to the realization of the ideas of the elites, breaking with its past and enhancing its innovative character compared to other Brazilian municipalities. In a legal context for standardization, Juiz de Fora equipped itself with instruments to regulate and discipline its changing space. By being based on incorporated hygienist/sanitary precepts, the Urban Legal Mechanisms confronted the modernization of the city and environmental obstacles. The Paraibuna River, a fundamental element in choosing the positioning of Juiz de Fora and delineating its expansion axis, became a preponderant actor and a channel for discussions, proposals and actions that put urban health on the agenda. Thus, the articulations for the institutionalization of the health issue, the urban plans and specific interventions promoted the idea of urban planning in the city. In view of the above, we sought to understand the role of the hygienist/sanitary movement in shaping physical-spatial standards through the analysis of the body of legal measures and specific actions to sanitize urban space and modify the natural environment between 1887 and 1942, providing contributions to the field of Urban Environmental History and Urban Historical Geography. The theoreticalmethodological assumptions of “Envirotech” were used to analyze how nature, political structures and technical infrastructures are intertwined in shaping the city. The empirical source is the documentary survey, covering various newspapers, medical bulletins, urban plans, graphic representations and legislative/normative texts. The research results made it possible to prove the thesis that the Paraibuna River has become a central axis for the development of strategies that aim not only to control its adverse effects of unhealthiness, but also to take advantage of its natural characteristics in an efficient way to maximize technological systems. existing environmental conditions. The recurring floods of the Paraibuna River, rather than merely posing a threat, became an impetus for the review and improvement of public health policies, planning and expansion of Juiz de Fora.